2016
DOI: 10.1177/1081286516651324
|View full text |Cite
|
Sign up to set email alerts
|

In plane shear and bending for first gradient inextensible pantographic sheets: numerical study of deformed shapes and global constraint reactions

Abstract: The aim of the present paper is the analysis of a two-dimensional continuum with two families of inextensible fibers that are orthogonal in the initial configuration. In the first part of the work, a new formulation is presented, in which the problem is reduced to a standard nonlinear constrained minimization, while in the second part of the work several numerical investigations are presented considering different boundary conditions with respect to standard symmetric bias extensional tests. The conceptual fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 79 publications
(117 reference statements)
1
17
0
Order By: Relevance
“…Numerical results [37][38][39][40][41] show that the final configurations obtained by using second gradient energies are smoother than those with the first gradient approach. In the following, numerical results will be reported for standard bias extension, shear and rotation tests, which confirm such a statement.…”
Section: Pipkin Elastic Plate Model With Inextensible Fibersmentioning
confidence: 94%
“…Numerical results [37][38][39][40][41] show that the final configurations obtained by using second gradient energies are smoother than those with the first gradient approach. In the following, numerical results will be reported for standard bias extension, shear and rotation tests, which confirm such a statement.…”
Section: Pipkin Elastic Plate Model With Inextensible Fibersmentioning
confidence: 94%
“…The mechanical systems which could be described by the introduced discrete model include those considered and studied in [2,4,5,10,11]. Indeed, (1) the pivots interconnecting (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, we believe that the potential scope of the presented model is wider: it very likely may include the most relevant deformation phenomena in the woven fabrics described in [12][13][14][15][16][17][18][19]. Indeed, the fibers constituting these fabrics intersect one with the others very similarly than in pantographic structures, and in their deformation, one can still distinguish extension, bending and shear: even if the hypothesis of elastic behavior in woven fabrics is applicable in a smaller range of deformation states, the model presented here seems capable of catching some relevant aspects of its phenomenology.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review on the modeling of pantographic structures can be found in [61,62]. Several results of numerical investigations can be found in [30,[63][64][65][66][67][68][69][70][71], while for an outline of recent experimental results we refer to [72,73]. The work is organized in the following way.…”
Section: Introductionmentioning
confidence: 99%